ANALYSIS OF THE INFLUENCE OF COMPENSATION, COMPETENCY, WORK MOTIVATION, AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE (CASE STUDY AT PT BANK SYARIAH INDONESIA, Tbk SEMARANG PANDANARAN BRANCH OFFICE) - Kamila, Dhea Beta Syafa; Sam'ani, Sam'ani -; Ulya, Nur Maziyah (Politeknik Negeri Semarang, 2024)
This study aims to analyze and obtain empirical evidence regarding the effect of compensation, competence, work motivation, and organizational culture on employee performance in Bank Syariah Indonesia Semarang Pandanaran Branch Office either simultaneously or partially. The population of the data used in this study includes all employees consisting of PT Bank Syariah Indonesia Semarang, Tbk Pandanaran Branch Office as many as 55 employees. Sampling technique using saturated sampling, primary data obtained through the distribution of questionnaires. The data analysis model uses multiple linear regression analysis model. Meanwhile, the data analysis technique used the F statistical test, the Coefficient of Determination (R 2 ) test, and the t statistical test. The results of the analysis show that simultaneously variables compensation, competence, work motivation, and organizational culture have a significant effect on employee performance at Bank Syariah Indonesia Semarang Pandanaran Branch Office. Partially, variable competencies, work motivation, and organizational culture significantly influenced employee performance, but variable compensation partially did not have any significant effect on employee performance at Bank Syariah Indonesia Semarang Pandanaran Branch Office.